Handling of hazardous drugs – Effect of an innovative teaching session for nursing students. (February 2017) - Zimmer, Janine; Hartl, Stefanie; Standfuß, Katrin; Möhn, Till; Bertsche, Astrid; Frontini, Roberto; Neininger, Martina P.; Bertsche, Thilo
Abstract: Background: Imparting knowledge and practical skills in hazardous drug handling in nursing students' education is essential to prevent hazardous exposure and to preserve nurses' health. Objectives: This study aimed at comparing routine nursing education with an additional innovative teaching session. Design: A prospective controlled study in nursing students was conducted in two study periods: (i) a status-quo period (routine education on handling hazardous drugs) followed by (ii) an intervention period (additional innovative teaching session on handling hazardous drugs). Settings/Participants: Nursing students at a vocational school were invited to participate voluntarily. Methods: In both study periods (i) and (ii), the following factors were analysed: (a) knowledge of hazardous drug handling by questionnaire, (b) practical skills in hazardous drug handling (e.g. cleaning) by a simulated handling scenario, (c) contamination with drug residuals on the work surface by fluorescent imaging. Results: Fifty-three nursing students were enrolled. (a) Median knowledge improved from status-quo (39% right answers) to intervention (65%, p < 0.001), (b) practical skills improved from status-quo (53% of all participants cleaned the work surface) to intervention (92%, p < 0.001). (c) Median number of particles/m 2 decreased from status-quo to intervention (932/97, p < 0.001). Conclusions: Compared with routine education, knowledge and practical skills in hazardous drug handling were significantly improved after an innovative teaching session. Additionally, the amount of residuals on the work surface decreased. This indicates a lower risk for hazardous drug exposure. Highlights: Effective nursing students' education on hazardous drugs prevents exposure. We compared routine nursing students' education and an innovative teaching session. We assessed knowledge by questionnaire and practical skills in a simulated scenario. The impact on workplace contamination was pursued by fluorescent imaging. The innovative training improved handling competence, i.e. occupational safety.